Effects of Serendipita indica on the Morphological and Physiological Characteristics of Agrostis stolonifera L. Under Drought Stress - Chuhong Lin; Wenxu Hu; Xin Qin; Yongjun Fei; Die Hu (Agronomy)
This study investigates the effect of Serendipita indica inoculation on the growth, structural characteristics of leaf epidermis, photosynthetic parameters, and antioxidant and osmoregulation capacities of Agrostis stolonifera L. under different drought stresses (normal moisture management: at 70–75% of the field capacity, low drought: at 55–60% field capacity, moderate drought: at 40–45% of the field capacity, and severe drought: at 25–30% of the field capacity). The results showed that inoculation with S. indica significantly enhanced the growth potential of A. stolonifera compared to uninoculated controls, and then under drought stress conditions, inoculation with S. indica significantly alleviated the inhibition of the growth and development of A. stolonifera, especially under mild and moderate drought stresses. These improvements were evident in both aboveground and underground parts, leaf relative water content, total root length, and root surface area after 25 days of drought treatments. Inoculated plants also exhibited higher levels of photosynthetic pigments, net photosynthetic rate (Pn), stomatal conductance (Gs), and transpiration rate (Tr) under drought conditions. Additionally, S. indica inoculation significantly increased the activities of catalase (CAT), peroxidase (POD), and ascorbate peroxidase (APX), as well as the soluble sugar, soluble protein, and proline levels under drought-stressed and non-stressed conditions. In addition, the increases in the malondialdehyde (MDA) content and relative conductivity (RC) of leaves were significantly lower in the inoculated group compared to the control group. In conclusion, the symbiosis with S. indica promotes the growth of A. stolonifera under drought stress, likely by enhancing photosynthesis, osmoregulatory substances, and antioxidant enzyme activities.